Imunofan—RDKVYR Peptide—Stimulates Skin Cell Proliferation and Promotes Tissue Repair - Sawicka, Justyna (Molecules, 2020)
Regeneration and wound healing are vital to tissue homeostasis and organism survival. One of the biggest challenges of today’s science and medicine is finding methods and factors to stimulate these processes in the human body. Effective solutions to promote regenerative responses will accelerate advances in tissue engineering, regenerative medicine, transplantology, and a number of other clinical specialties. In this study, we assessed the potential efficacy of a synthetic hexapeptide, RDKVYR, for the stimulation of tissue repair and wound healing. The hexapeptide is marketed under the name “Imunofan” (IM) as an immunostimulant. IM displayed stability in aqueous solutions, while in plasma it was rapidly bound by albumins. Structural analyses demonstrated the conformational flexibility of the peptide. Tests in human fibroblast and keratinocyte cell lines showed that IM exerted a statistically significant (p < 0.05) pro-proliferative activity (30–40% and 20–50% increase in proliferation of fibroblast and keratinocytes, respectively), revealed no cytotoxicity over a vast range of concentrations (p < 0.05), and had no allergic properties. IM was found to induce significant transcriptional responses, such as enhanced activity of genes involved in active DNA demethylation (p < 0.05) in fibroblasts and activation of genes involved in immune responses, migration, and chemotaxis in adipose-derived stem cells derived from surgery donors. Experiments in a model of ear pinna injury in mice indicated that IM moderately promoted tissue repair (8% in BALB/c and 36% in C57BL/6 in comparison to control).